Kajian Pengembangan Kawasan Insdustri Di Desa Pandai Besi Ngingas, Waru Sidoarjo - Tisa Angelia; Ikamto Budiman; Clara Sarti Widiwati; I Komang Kerthajaya (Universitas Merdeka Surabaya, 2024)
The purpose of this community service is to find out what the Ngingas Region is, the Disadvantages and Advantages of Ngingas and the Potential to be developed. The implementation was carried out in Waru Sidoarjo. Waru District as an area dense with industrial sectors, there is a metal processing industry center that grows in the midst of local community life. The location of the growth of the metal industry center is in Ngingas Village, Kureksari Village, and also Kedungrejo Village. An industrial center is an area that is identical to a grouping of types of industries that have similarities both in terms of raw materials and finished goods whose production in an area, from the beginning of its emergence has been deeply rooted for a long time in the area and has brought its influence from the existence of the metal center to the pattern of community life activities around it. Such as the existence of the metal processing industry center in Waru District which has existed since 1978.